Microstructurally driven self-sharpening mechanism in beaver incisor enamel facilitates their capacity to fell trees. (1st March 2023) - Hunt, Tyler C.; Grejtak, Tomas; Kodangal, Deeksha; Varma, Soumya; Rinaldi, Caroline E.; Pathak, Siddhartha; Krick, Brandon A.; Erickson, Gregory M.
Abstract: Beavers ( Castor ) stand out among mammals for their unique capacity to fell trees using their large, ever-growing incisors. This routine consumption of resistant fodder induces prodigious wear in the lower incisors, despite this blunting effect the incisors maintain a remarkably sharp cutting edge. Notably, the enamel edges of their incisors show a highly complex two-part microstructure of which the biomechanical import is unknown. Here, using fracture analysis, nanoindentation, and wear testing on North American beaver ( C. canadensis ) incisors we test the microstructure's possible contribution to maintaining incisal sharpness. Although comparable in hardness, the inner enamel preferentially fails and readily wears at 2.5 times the rate of the outer enamel. The outer microstructure redirects all fractures in parallel, decreasing fracture coalescence. Conversely, the inner microstructure facilitates crack coalescence increasing the wear rate by isolating layers of enamel prisms that readily fragment. Together these two architectures form a microstructurally driven self-sharpening mechanism contained entirely within the thin enamel shell. Our results demonstrate that enamel microstructures exposed at the occlusal surface can markedly influence both enamel crest shape and surface texture in wearing dentitions. The methods introduced here open the door to exploring the biomechanical functionality and evolution of enamel microstructures throughout Mammalia. Statement of significance: Enamel microstructure varies significantly with the diversity of diets, bite forces, and tooth shapes exhibited by mammals. However, minimal micromechanical exploration of microstructures outside of humans, leaves our understanding of biomechanical functions in a nascent stage. Using biologically informed mechanical testing, we demonstrate that the complex two-part microstructure that comprises the cutting edge of beaver incisors facilitates self-sharpening of the enamel edge. This previously unrecognized mechanism provides critical maintenance to the shape of the incisal edge ensuring continued functionality despite extreme wear incurred during feeding. More broadly, we show how the architecture of prisms and the surrounding interprismatic matrix dictate the propagation of fractures through enamel fabrics and how the pairing of enamel fabrics can result in biologically advantageous functions. Graphical abstract: Image, graphical abstract